Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.